Spectrophotometric enzymatic cycling method using L-glutamate dehydrogenase and D-phenylglycine aminotransferase for determination of L-glutamate in foods - Wanida Khampha (2018)
This report describes a new spectrophotometric method capable of determining low levels of L-glutamate. The assay is based on substrate cycling between L-glutamate dehydrogenase (GlDH) and the novel enzyme D-phenylglycine aminotransferase (D-PhgAT). In this system, GlDH converts L-glutamate to 2-oxoglutarate with concomitant reduction of NAD+to NADH. The 2-oxoglutarate is recycled to L-glutamate in a transamination reaction catalyzed by D-PhgAT using D-4-hydroxyphenylglycine as an amino donor, which is converted to 4-hydroxybenzoylformate. Both NADH and 4-hydroxybenzoylformate strongly absorb UV light at 340 nm (ε340 nm=6.22×103and 8.90×103l mol-1cm-1, respectively). The signal amplification effect of the cycling reactions is thus further enhanced by the combined absorption of the two accumulating reaction products. The standard calibration curve for L-glutamate was linear from 0.2 to 20 μM, with a detection limit of 0.14 μM. Food samples can be significantly diluted before subjected to the assay, thus reducing the effects of interfering substances. Because of the unique substrate specificity of D-PhgAT, L-glutamate could be selectively determined in the presence of other common amino acids at relatively high concentrations. The assay was satisfactorily applied to measure L-glutamate in various kinds of food products. The procedure is simple, rapid, accurate, and should be easily automated. © 2004 Elsevier B.V. All rights reserved.